2017
DOI: 10.1039/c7nr05216b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced blood brain barrier permeability and glioblastoma cell targeting via thermoresponsive lipid nanoparticles

Abstract: Thermoresponsive targeting is used to deliver therapeutic agents at hyperthermic conditions (39-45 °C). However, available thermoresponsive drug delivery systems (TDDS), including liposomes, have a complex method of preparation involving toxic solvents and reagents. The objective of this in vitro study was to prepare and characterize thermoresponsive lipid nanoparticles (TLN) for treating glioblastoma, the most aggressive brain tumor whose treatment is limited by a low blood brain barrier (BBB) permeability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…46,47,63 We demonstrated that our BBB model had positive barrier functions to block PTX and BTZ transportation to work on the GBM cells underneath, which is similar to the limited therapeutic effects of PTX and BTZ on GBM in vivo. 64,65 Our results also demonstrated that a lower dose of PTX and BTZ had a slight effect on the TEER value of the BBB model, with a short time period of administration, whereas a higher dose significantly affected the BBB integrity. During the AD progression, BBB plays an important role in regulating the dynamic balance of A β in the brain.…”
Section: Discussionsupporting
confidence: 63%
“…46,47,63 We demonstrated that our BBB model had positive barrier functions to block PTX and BTZ transportation to work on the GBM cells underneath, which is similar to the limited therapeutic effects of PTX and BTZ on GBM in vivo. 64,65 Our results also demonstrated that a lower dose of PTX and BTZ had a slight effect on the TEER value of the BBB model, with a short time period of administration, whereas a higher dose significantly affected the BBB integrity. During the AD progression, BBB plays an important role in regulating the dynamic balance of A β in the brain.…”
Section: Discussionsupporting
confidence: 63%
“…The ability of LMNVs to cross an in vitro BBB model was preliminarily investigated (Fig. 6), as previously reported in the literature 44. Briefly, two-compartment BBB models consisting of porous scaffolds (with pores of 3 μm diameter) were used to culture brain endothelial cells (BEC) at high confluence.…”
Section: Resultsmentioning
confidence: 99%
“…Multifunctionalized theragnostic systems have various abilities ranging from tumor targeting and cell penetration to real time monitoring. Specifically, to further enhance BBB permeability and targeting of GBM, nanoparticles could also be responsive to different stimuli such as pH (Tao et al, ), redox (X. Zhu et al, ), temperature (Rehman et al, ; Turabee, Jeong, Ramalingam, Kang, & Ko, ), magnets and ultrasound (Raucher, Dragojevic, & Ryu, ). In this section, we outline recent examples of novel and advanced nanosystem for GBM multimodal therapy and imaging.…”
Section: Nanotechnology‐based Therapy and Imaging For Glioblastomamentioning
confidence: 99%